Detection of Concussion Using Cranial Accelerometry. - Auerbach, Paul S.; Baine, Jennifer G.; Schott, Megan L.; Greenhaw, Amy; Acharya, Monika G.; Smith, Wade S. (Clinical Journal of Sport Medicine, 2015)
Objective: To determine whether skull motion produced by pulsatile cerebral blood flow, as measured by cranial accelerometry, is altered during concussion. Design: In phase 1, to identify a specific pattern indicative of concussion, cranial accelerometry of subjects who sustained a concussion underwent analysis of waveforms, which was compared with accelerometry from subjects without a concussion (baseline). In phase 2, this concussion pattern was tested against prospectively acquired, blinded data. Setting: High school tackle football practice and game play. Participants: Eighty-four football players. Interventions: Subjects had accelerometry measurements and concurrent 2-lead electrocardiograms. In players with a concussion, multiple sequential measurements were obtained. Sport Concussion Assessment Tool 2 was used to assist clinical determination of concussion. Main Outcome Measures: Whether a characteristic waveform pattern of cranial accelerometry occurs in subjects with concussion. Results: Phase 1 demonstrated a consistent pattern correlated to concussion. Phase 2 found this pattern in 10 of 13 subjects with concussion (76.9% sensitivity). Seventy-nine of 82 baseline plus nine postseason (total = 91) recordings from nonconcussed subjects did not show the concussion pattern (87% specificity). Conclusions: In subjects with concussion, we observed a unique pattern determined by cranial accelerometry. This may provide a method to noninvasively detect and longitudinally observe concussion. Clinical Relevance: There is no objective, real-time, noninvasive, and easily accessible measure for concussion. If accelerometry is validated, it could provide a critical diagnostic tool for sports medicine physicians.